Multiple‐wavelength sensing of Jupiter during the Juno mission's first perijove passage. Issue 10 (25th May 2017) - Orton, G. S.; Momary, T.; Ingersoll, A. P.; Adriani, A.; Hansen, C. J.; Janssen, M.; Arballo, J.; Atreya, S. K.; Bolton, S.; Brown, S.; Caplinger, M.; Grassi, D.; et al.
Abstract: We compare Jupiter observations made around 27 August 2016 by Juno's JunoCam, Jovian Infrared Auroral Mapper (JIRAM), MicroWave Radiometer (MWR) instruments, and NASA's Infrared Telescope Facility. Visibly dark regions are highly correlated with bright areas at 5 µm, a wavelength sensitive to gaseous NH3 gas and particulate opacity at p ≤5 bars. A general correlation between 5‐µm and microwave radiances arises from a similar dependence on NH3 opacity. Significant exceptions are present and probably arise from additional particulate opacity at 5 µm. JIRAM spectroscopy and the MWR derive consistent 5‐bar NH3 abundances that are within the lower bounds of Galileo measurement uncertainties. Vigorous upward vertical transport near the equator is likely responsible for high NH3 abundances and with enhanced abundances of some disequilibrium species used as indirect indicators of vertical motions. Key Points: A high correlation between visibly dark clouds and 5‐micron radiation extends only partially to microwave radiation Five‐micron spectroscopy and microwave radiometry yield a 5‐bar NH3 abundance not inconsistent with Galileo results Meridional dependence of deep atmospheric opacity is dynamically consistent with most other vertical‐motion tracers Plain Language Summary: Comparison of observations of Jupiter by different Juno and ground‐based instruments verified some long‐standing relationships, such as those between visibly dark regions and clear, dry parts of the atmosphere. But Juno saw significant exceptions. Different instrument results for the abundance of ammonia gas, a condensate similar to water in the Earth's atmosphere, at 5 bars of pressure were self‐consistent and within the uncertainty of Galileo results. The substantial upwelling of ammonia detected by the Microwave Radiometer from great depth near the equator is consistent with other indirect tracers of vertical winds.